AN ANALYSIS OF POLITENESS STRATEGIES IN ACTORS ON ACTROS PROGRAM ON VARIETY’S YOUTUBE CHANNEL - Hafizah, Nurul; Nazara, Wa’özisökhi (LINGUA LITERA : journal of english linguistics and literature, 2024)
This research aims to identify the types of politeness strategies in the Actors onActors program on Variety’s YouTube channel. The research data were from theActors on Actors program on Variety’s YouTube channel. The writer appliedLeech’s (1983) theory to classify politeness strategies. There are six types ofpoliteness strategies. They are the approbation maxim, agreement maxim, modestymaxim, sympathy maxim, tact maxim, and generosity maxim. This research wasqualitative. This study reveals that all types of politeness strategies according toLeech (1983) were found in the Actors on Actors program on Variety’s YouTubechannel. The types are approbation maxim, agreement maxim, modesty maxim,sympathy maxim, tact maxim, and generosity maxim. From all types of politenessstrategies, it was found that the most common politeness strategy was theapprobation maxim. In conclusion, it can be said that the Actors on Actors programused all types of politeness strategies in the Variety’s YouTube channel.